How Iconic Communication affects the brand loyalty in cafeterias via brand experience and moments of truth: The case of Starbucks - Anayiotos, Constantinos (q, 2021)
The present dissertation named ‘’How Iconic Communication affects the brand loyalty in cafeterias via brand experience and moments of truth. The case of Starbucks’’ is written by Constantinos Anayiotos, student at the 4th grade of the Department of Communication and Internet studies from Cyprus University of Technology under the supervision of Dean Mr. George Panigyrakis. The purpose of the following quantitative study is to examine how customer-journey in cafeterias is leading to brand loyalty. Brand loyalty is being made by brand experience and the moments of truth. These two constructs have various touch points and these touch points are able to make a customer brand loyal. Consequently, the present study aims to examine how two different constructs, brand experience and moments of truth, can be linked, in an integrated construct which measures consumers loyalty towards a specific brand of cafeteria. In literature, brand experience has been mainly studied in areas in which brand-related stimulus affect consumers' perceptions about the image of the brand, whereas the moments of truth have been used to measure the one-to-one interaction in the area of services. In this study, an integrated theoretical model is implemented, by which experiences are conceptualized through the customer’s journey linking both the experiential aspects of the brand but also their service-related aspects of communication. In order to examine the above aim online questionnaires were used. Finally, the research revealed that moments of truth are more influential than the brand experience towards brand loyalty and that additional attention should be given to holistic experience that consumers receive, at least in the Cypriot community.
Keywords: Experiential Marketing; Brand Experience; Moments of Truth; Brand Loyalty